If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6p + -4 = 10p Reorder the terms: -4 + 6p = 10p Solving -4 + 6p = 10p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-10p' to each side of the equation. -4 + 6p + -10p = 10p + -10p Combine like terms: 6p + -10p = -4p -4 + -4p = 10p + -10p Combine like terms: 10p + -10p = 0 -4 + -4p = 0 Add '4' to each side of the equation. -4 + 4 + -4p = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -4p = 0 + 4 -4p = 0 + 4 Combine like terms: 0 + 4 = 4 -4p = 4 Divide each side by '-4'. p = -1 Simplifying p = -1
| 10y-8y^3= | | 15N-50=10 | | 12n^3+84n^2=0 | | 1000x=325/999 | | -8x+6=-x+4 | | 12_41/6 | | M/4=13/8 | | 1.77+9.1y=3.2y | | 100x=26/99 | | 8w-22=25 | | 2ln(x-4)=ln(x+2)+ln(x+9) | | -27=8x-9-2x | | 10x=4/9 | | 2(u-2)-6u= | | 6w-1-8w=-9 | | 30-3/5x=x= | | .3x+.4y=1 | | 40p^3-70p^2=0 | | -7(x+1)-3=-2(3x+6) | | 4p=4p | | -7(x+1)-3=-2(3a+6) | | 7p+12+p=16 | | 10m-m=9 | | 30-3/5x= | | 5/6*14 | | 4.22(-6.6x-7.7)=-113.2648 | | 3x-8(6x-1)= | | -n+5=-n | | 2(y+8)=2y-6 | | -6k-3k=27 | | 0(x)=12x+1 | | b1/2 |